BRANDING STRATEGY OF VILLAGES OUTSIDE JAVA IN INCREASING MARKET AWARENESS - Mohammad Ikhsan Kurnia; Yusuf Amri Amrullah (FEB Universitas Sam Ratulangi Manado, 2024)
Indonesia is a very rich country, not only in terms of its natural resources, but also in terms of the creativity of the people. Most villages in Indonesia have a diversity of culture, arts, crafts, culinary delights and historical heritage. The potential of villages in Indonesia is not actually concentrated on the island of Java as the most densely populated area, but villages outside Java also have enormous potential if managed well. There are several villages that are well known, but there are still many of them not yet known by the markets outside their region. This makes researchers feel compelled to study village branding owned by villages outside Java. With a qualitative approach, researchers used a literature review method on literature about branding villages outside Java which was documented on the Garuda Platform. This research succeeded in reviewing 9 existing literature titles and discovered the fact that most of the villages studied did not have a strong village brand. Keywords: Village, Brand, Outside Java, Literature Review.